Antiviral properties and molecular docking studies of eco-friendly biosynthesized copper oxide nanoparticles against alfalfa mosaic virus - Dalia G. Aseel; Mona Rabie; Ali El-Far; Ahmed Abdelkhalek (BMC Plant Biology)
Abstract Background Nanotechnology has been recognized as a viable technology for enhancing agriculture, particularly in the plant pathogen management area. Alfalfa mosaic virus (AMV) is a global pathogen that affects many plant species, especially economically valuable crops. Currently, there is less data on the interaction of nanoparticles with phytopathogens, particularly viruses. The current study looked into how copper oxide nanoparticles (CuO-NPs)-mediated Haloxylon salicornicum aqueous extract can fight AMV infections on tobacco plants. Results Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analyses showed that CuO-NPs have a spherical and hexagonal structure ranging from 20 to 70 nm in size. Fourier transform infrared spectroscopy (FTIR) analysis showed that the produced CuO-NPs have many functional groups and a lot of secondary plant metabolites. Under greenhouse conditions, the foliar application of CuO-NPs (100 ppm) enhanced tobacco growth and decreased viral symptoms. Treatment with CuO-NPs 48 h before (protective treatment) or 48 h after (curative treatment) AMV infection significantly reduced AMV accumulation levels by 97%. Additionally, the levels of total chlorophyll, phenolic, and flavonoid contents, as well as DPPH, exhibited a significant increase in tobacco leaves 30 days after inoculation in comparison to untreated plants. Moreover, considerable differences in levels of different antioxidant enzymes, including SOD, PPO, POX, and CAT, were also observed. On the other hand, the oxidative stress markers (MDA and H2O2) were significantly reduced in CuO-NPs-treated plants compared with non-treated plants. It was also found that the protective treatment increased the expression levels of genes involved in the jasmonic pathway (JERF3 and WRKY1). On the other hand, the curative treatment increased the expression levels of polyphenolic pathway acid (CHI and HQT) and the SA-signaling pathway genes (PR-2 and POD). The study of molecular docking interactions with four AMV target proteins showed that CuO-NPs had high binding energy with the viral replication protein 1a, measured at -3.2 kcal/mol. The binding with these proteins can suppress AMV replication and spread, potentially clarifying the mechanism behind the antiviral effect. Conclusions The overall analysis results indicate that the curative treatment is more influential and successful than the protective treatment in combating AMV infection. Consequentially, CuO-NPs could potentially be employed in foliar sprays for the effective and environmentally friendly management of plant virus infections.